Validating a novel capability of assessing pathways of animal water gain and loss - Zachary T. Steele; Karen Caceres; Zachary A. David; Lisa M. Shollenberger; Alexander R. Gerson; Seth D. Newsome; John P. Whiteman (Royal Society Open Science)
Understanding variations in the routes by which wild animals gain and lose water is challenging, and common methods require longitudinal sampling, which can be prohibitive. However, a new approach uses Δ′17OBW (Δ′17O of animal body water), calculated from measurements of δ′17O and δ′18O in a single sample, as a natural tracer of water flux. Δ′17OBW is promising, but its relationship to organismal variables such as metabolic rate and water intake have not been validated. Here, we continuously measured oxygen influxes and effluxes of captive deer mice (Peromyscus maniculatus), and manipulated their water intake and metabolic rate. We used these oxygen flux data to predict Δ′17OBW for the mice and compared these model predictions with Δ′17OBW measured in blood plasma samples. As expected, Δ′17OBW positively correlated with drinking water intake and negatively correlated with metabolic rate. All predicted Δ′17OBW (based on measured oxygen fluxes) values differed from measured Δ′17OBW values by <30 per meg (mean absolute difference: 11 ± 9 per meg), suggesting high accuracy for this modelling approach because studies currently report a range of 300 per meg for Δ′17OBW among mammals, birds and fish.